Occurrence and behavior of per‐ and polyfluoroalkyl substances from aqueous film‐forming foam in groundwater systems. Issue 2 (12th March 2018) - Hatton, Jim; Holton, Chase; DiGuiseppi, Bill
Abstract: Per‐ and polyfluoroalkyl substances (PFAS) are fluorinated compounds and the active ingredient in aqueous film‐forming foam (AFFF). AFFF has been identified as a significant source of PFAS contamination in groundwater. PFAS are also present in many other industrial and consumer products and their manufacture and use has led to numerous contaminated sites. Human health risks have been identified with studies linking firefighter cancers to training facilities where AFFF was used. Given the widespread release of these compounds to the environment and their potential health risks, understanding their mobility characteristics is important. This article details the occurrence and behavior of these substances in groundwater systems to help guide the emerging fields of PFAS investigation and remediation. Background is presented on AFFF and PFAS source characteristics, including common industrial and consumer PFAS sources. In addition, chemical properties, sorption and retention parameters, and observed transformation properties of PFAS and related compounds are discussed. Finally, knowledge gaps are identified for future laboratory and field studies.